A technological quality control system for rice supply chain - Qi Tao; Zhenyu Cai; Xiaohui Cui (Food and Energy Security, 2023)
Abstract Rice quality affects social stability, consumer health, and corporate brand benefit. The traditional supply chain traceability management system is centralized, monopolized, asymmetric, and opaque. It is the main factor leading to frequent food safety incidents. This paper proposes a technological quality control system for rice supply chain to protect rice products quality and safety. Firstly, it adopts risk assessment and traceability mechanism to prevent the hazard factors in the production and processing. Then, to prevent spoiled food from endangering the consumers’ health and reduce food waste, it explores a shelf life model of rice products to predict the remaining shelf life of products. Finally, this paper constructs a decentralized traceability management system based on blockchain and IoT, which enables consumers to access the real information of rice products and helps supervisors to monitor the quality of products in the supply chain.